2005
DOI: 10.1093/humrep/dei264
|View full text |Cite
|
Sign up to set email alerts
|

The acceptability of posthumous human ovarian tissue donation in Utah

Abstract: This study substantiates the ethical recommendation that explicit prior written consent of the donor be obtained when ovarian tissue donations are procured for fertilization, or transfer of a preembryo to cause a pregnancy. In light of the rapid technological advancements in ovarian follicle/oocyte cryopreservation and maturation, the time may have come to provide potential organ donors the opportunity to specify their desires regarding ovarian tissues when registering for organ donation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
4
0
3
Order By: Relevance
“…The authors compared attitudes toward organ donation and assisted reproduction in general. They found that more than half of surveyed subjects supported using donated oocytes posthumously for establishing a pregnancy (10). These data are in contrast to a study published in the United Kingdom, in which only 28% of participants found posthumous donation acceptable for purposes of research or treatment (11).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The authors compared attitudes toward organ donation and assisted reproduction in general. They found that more than half of surveyed subjects supported using donated oocytes posthumously for establishing a pregnancy (10). These data are in contrast to a study published in the United Kingdom, in which only 28% of participants found posthumous donation acceptable for purposes of research or treatment (11).…”
Section: Discussionmentioning
confidence: 72%
“…In 2005, Mizukami et al (10) published a survey study regarding the attitudes toward posthumous donation of oocytes for research or reproduction in 704 Utah residents. The authors compared attitudes toward organ donation and assisted reproduction in general.…”
Section: Discussionmentioning
confidence: 99%
“…One such study focused on posthumous donation of female gametes to unknown recipients and found that, among a representative sample of Utah residents, 57% of respondents "were comfortable donating their own or partner's oocytes for fertilization and transfer of the resulting embryos to a couple desiring pregnancy" in the event of death [9]. Another study of couples presenting for their first fertility consultation in New York found that 85% of males and 72% of females "would permit their spouse to harvest their [own] eggs/sperm for the purpose of conceiving a child after their death" [10].…”
Section: Introductionmentioning
confidence: 99%
“…La finalidad de los crioprotectores es mantener la viabilidad celular durante un periodo determinado, previniendo el daño celular durante el proceso de congelación y descongelación, con características tales como: solubles en soluciones acuosas de electrolitos, atravesar las membranas celulares y no ser tóxicos a altas concentraciones (Vincet et al, 1998;Mizukami et al, 1999) El crioprotector no solo está diseñado para la prevención de la criogenesis sino para ayudar a la célula espermática a iniciar la movilidad, subsecuentemente cuando el espermatozoide empieza a mover el flujo de ATP hacia el flagelo con corta duración (Oda y Morisawa, 1993;Ohta et al, 1997).…”
Section: Agentes Crioprotectoresunclassified